2017
DOI: 10.1007/s00167-017-4520-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of radiological measurements of trochlear dysplasia; a literature review

Abstract: V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 24 publications
1
72
0
1
Order By: Relevance
“…Eight established parameters of limb alignment and patellar tracking were assessed as previously published. 7,9,12,17,21,2830…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight established parameters of limb alignment and patellar tracking were assessed as previously published. 7,9,12,17,21,2830…”
Section: Methodsmentioning
confidence: 99%
“…Using a diagnostic threshold of 11°, this measure has shown a sensitivity of 93% and a specificity of 87% for trochlear dysplasia 6 and is recommended for use in the assessment of trochlear dysplasia. 28…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 27 , 31 Because the LTI is an MRI measurement, it better characterizes the proximal trochlea, which is an area difficult to appreciate on conventional radiographs as is attempted using the Dejour radiographic classification. 5 , 23 , 25 , 32 Also, LTI provides a quantitative description of dysplasia. Carrillon et al 5 reported that an LTI of < 11° is associated with a 95% specificity of having PI secondary to TD.…”
mentioning
confidence: 99%
“…The distance from this line to the deepest part of the trochlea was determined in a similar way to the trochlear depth. [10] The trochlear facet asymmetry was determined by measuring the medial (MT) and lateral (LT) trochlea facet lengths 30 mm above the axial cross-section of the articular line and proportioned to each other. [11] The lateral trochlear inclinations (LTI) were determined by measuring the angle between the posterior femoral condyles and the lateral facet with the Cobb method in the most superior axial MR section.…”
Section: Radiographic Assessment and Reliability Of Measurementsmentioning
confidence: 99%
“…[11] The sulcus angle was determined on the axial MR sequence at the level of the deepest depression of the intercondylar groove by measuring the angle between the ventral articular surfaces of the medial and lateral condyle. [10] The patellar tilt angle (PTA) was determined by drawing a line along the lateral joint surface of the patella and a line drawn along the posterior condylar line using the Cobb method feature of the picture archiving and communication system (PACS) program. [12] Medial plicae thickness was measured on the axial MRI images by using the magnifying feature of the program.…”
Section: Radiographic Assessment and Reliability Of Measurementsmentioning
confidence: 99%